Good Corporate Governance, Corporate Social Responsibility, Firm Value, and Financial Performance as Moderating Variable - Mukhtaruddin Mukhtaruddin; Ubaidillah Ubaidillah; Kencana Dewi; Arista Hakiki; Nopriyanto Nopriyanto (Indonesian Journal of Sustainability Accounting and Management, 2019)
Good corporate governance and corporate social responsibility can assist the company in facing the challenges and risks as a strategy in increasing the firm value by building the right image from the stakeholders’ view. This study aims to determine the effect of good corporate governance and corporate social responsibility on firm value with financial performance as a moderating variable. The population of this research is banking companies listed in Indonesia Stock Exchange (IDX) for 2011–2015. The sample consisted of 23 companies which were selected by purposive random sampling. This data is analyzed by using Partial Least Square approach. The results of this study indicate that good corporate governance has an insignificant positive effect on firm value; otherwise corporate social responsibility has a significant negative impact on firm value. Financial performance has significantly strengthened the relationship between good corporate governance and corporate social responsibility on firm value.